The Phenomenon of School Dropouts in the Pujut, Mandalika SEZ: An Interpretive Phenomenological Analysis from the Perspective of Education Actors and Society - Agus Kurnia; Humamurrizqi; M. Zainuddin Abdul Hafiz; Jamaludin; Muhammad Safruddin (ASTEEC, 2024)
The development of the Mandalika Special Economic Zone (SEZ) in Pujut district, while driving economic growth, has raised concerns about declining school interest and high dropout rates among local students. This qualitative study, employing interpretive phenomenological methods, explores the experiences and perceptions of education actors, including the vice principal for student affairs, counseling guidance teachers, Mongge madrasah teachers, and the Head of Sukadana Village, to understand the underlying factors. Findings reveal economic constraints as a primary cause of dropout, with many students from low-income families unable to afford education. Early marriage, particularly among female students, is another significant factor influenced by economic, social, and cultural pressures. Additionally, broken homes, unsupportive social environments, the negative influence of social media, and a lack of motivation contribute to the problem. Schools have responded with counseling, parental engagement, and restrictions on mobile phone use. However, deeper issues like early marriage and broken homes necessitate broader interventions involving government policies and socio-cultural change. This research illuminates the complexity of school dropout in the Mandalika SEZ and highlights the need for a comprehensive approach engaging all stakeholders to ensure educational access and success for all students.